1997
DOI: 10.1111/j.1745-6584.1997.tb00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Axially Symmetric and Nonsymmetric Flow to a Well with MODFLOW, and Application to Goddard2 Well Test, Boise, Idaho

Abstract: Tools for analyzing aquifer test data at the pumping or injection well are limited for aquifer conditions that are not axially symmetric about the pumping well. Accurate simulations of head change at a pumping well can be generated with MODFLOW using a discretization scheme that (1) captures steep gradients adjacent to the cell(s) containing the pumping or injection well and (2) approximates radial flow despite rectangular prism well cell(s). This scheme is based on a very small incremental cell width adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 12 publications
0
19
0
4
Order By: Relevance
“…For determining the flow rate accurately, the cell dimension of 0.001 m is considered for the cells next to the drain periphery. To improve the model efficiency, the cell dimensions are gradually enlarged through getting far from the drain by an expansion factor of 1.44 (Barrash and Dougherty, 1997). The length of drain cells, along its axis and at its ends are 0.001 m and gradually increase toward the midpoint of the drain by extension factor of 1.44.…”
Section: The Flow Distribution Along the Horizontal Drainmentioning
confidence: 99%
“…For determining the flow rate accurately, the cell dimension of 0.001 m is considered for the cells next to the drain periphery. To improve the model efficiency, the cell dimensions are gradually enlarged through getting far from the drain by an expansion factor of 1.44 (Barrash and Dougherty, 1997). The length of drain cells, along its axis and at its ends are 0.001 m and gradually increase toward the midpoint of the drain by extension factor of 1.44.…”
Section: The Flow Distribution Along the Horizontal Drainmentioning
confidence: 99%
“…rectilinear rows and columns). Barrash and Dougherty [6] found that the FD formulation underestimated large head gradients that can occur in the vicinity of pumping (or injection) wells. Generally, a detailed representation of the flow field in the vicinity of hydrological features and through irregular hydrogeological units (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Barrash and Dougherty (1997) describe a variable grid refinement strategy through which a finite difference model can be discretized in order to better estimate the drawdown at a well. Various methods can be used to minimize s d when simulating drawdown at a pumping well.…”
Section: Introductionmentioning
confidence: 99%
“…This method was made available for MODFLOW 2005 (Mehl and Hill 2005). These grid refinement strategies would facilitate the implementation of Barrash and Dougherty's (1997) while decreasing the computational burden as compared to global or variable grid refinement approaches. These grid refinement strategies would facilitate the implementation of Barrash and Dougherty's (1997) while decreasing the computational burden as compared to global or variable grid refinement approaches.…”
Section: Introductionmentioning
confidence: 99%